Southern Hemisphere biodiversity and global change: Data gaps and strategies. (23rd August 2016) - Chambers, Lynda E.; Barnard, Phoebe; Poloczanska, Elvira S.; Hobday, Alistair J.; Keatley, Marie R.; Allsopp, Nicky; Underhill, Les G.
Abstract: Long‐term datasets needed to detect the impacts of global change on southern biodiversity are still scarce and often incomplete, challenging adaptation planning and conservation management. Biological data are probably most limited in arid countries and from the oceans, where natural environmental variability ('noise') means that long time series are required to detect the 'signal' of directional change. Significant national and international investment and collaboration are needed for most southern nations to reliably track biodiversity trends and improve conservation adaptation to rapid climate change. Emerging early warning systems for biodiversity, incorporating regional environmental change drivers, citizen science and regional partnerships, can all help to compensate for existing information gaps and contribute to adaptation planning.